Pelatihan Media Digital Berbasis Platform Canva Bagi Guru-Guru di SMA Negeri 3 Kejuruan Muda - Aulia Rahman; Anis, Madhan; Prasetyo, Okhaifi; Bukhari, Bukhari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity (PKM) aims to increase the competency in using Canva at SMA Negeri 3 Vocational Youth. This program was designed to overcome the challenges teachers at these schools face, who often experience obstacles in integrating digital technology into the learning process. Most teachers in these schools have not been optimal in designing learning media based on the Canva Platform, resulting in a lack of innovation in delivering material in class. The training method includes various stages, starting from licensing, preparation, and implementation, which will take place from 8 to 10 August 2024, to the monitoring and evaluation stage. In this training, 40 teachers took part in sessions covering the basics of using Canva, graphic design techniques for learning, and strategies for integrating technology into the curriculum. The pre-test and post-test were evaluated to assess the increase in participants' understanding. Evaluation results show an increase in participants' understanding of 38%, which shows that this training effectively improves teachers' digital skills. This increase has an impact on improving individual teachers' abilities and can potentially improve the quality of learning in schools as a whole. Continuing this training can encourage the development of teacher professionalism in facing future technological challenges and create an educational culture that is more open to digital innovation.